The value of play in the acquisition of a foreign language - Gómez , Yari Paola; Ortega, Galia Tatiana Ortega (Rastros Rostros, 2023)
The constant change in a globalized and dehumanized world, the deteriorating economic and social processes, the educational changes and the development of skills that enable competent men and women in multiple fields, make us think that as people advance culturally and technologically, the need to know other languages arises.